SCIENCE DEVELOPMENT STATISTICAL ANALYSIS IN HIGHER EDUCATION SECTOR - E. A. Dolgikh; L. S. Parshintseva (Вестник университета)
The main indicators, characterizing the science development in the higher education sector, have been considered. The main trends in changing the number of organizations engaged in research and development in this sector, as well as the number of personnel employed in them, have been analysed. Attention to the study of the movement of personnel in organizations has been paid. Information about availability of scientific degrees of candidate and doctor of sciences in scientific personnel in the higher education sector has been collected. The dynamics and structure of internal costs for research and development have been considered. The dynamics of the average monthly salary of personnel engaged in research and development in the higher education sector has been analysed.